ANALISIS INJEKSI EPOXY PADA PERBAIKAN RETAK BETON TERHADAP BEBAN LENTUR - Herlambang, Fajar Surya; Setyono, Evin Yudhi (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2018)
One of the causes of cracking in concrete beams is excessive gravitational load,mainly due to live loads that exceed capacity. The cracked beam can be repaired by the epoxy injection method but the condition of the repair is the strength value must reach the condition before cracking. The purpose of this study was to determine the effectiveness of injection in filling cracks and assessing epoxy ability in restoring beam strength. The specimen is a f'c 25 reinforced concrete block with dimensions of 15x15x60 cm. Tests are carried out with 2 methods, that are loading test according to SNI 03-4154-1996 and UPV. Load test and UPV were carried out at the age of 28 days and 3, 6. 9 days after epoxy injection. Based on the load test, epoxy injection is able to restore beam flexural strength up to 50% which is indicated by achieving load values after being injected. From the UPV test, it is known that epoxy injection is able to fill cracks which are characterized by increasing ultrasonic wave propagation speed on the test object after injection compared to when cracked but the injection cannot completely fill the cracked area which is indicated by a smaller wave propagation value than when the object the test has not experienced a crack. Based on a series of research activities, it is very necessary to pay attention to the injection process such as viscosity and injection pressure in order to obtain good results.Kata kunci : crack, injection, epoxy